2019
DOI: 10.15407/spqeo22.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Combination of thermionic emission and tunneling mechanisms to analyze the leakage current in 4H-SiC Schottky barrier diodes

Abstract: A new method to analyze reverse characteristics of 4H-SiC Schottky barrier diode has been presented in this paper. The model incorporates both the current induced by the tunneling of carriers through the Schottky barrier and that induced by the thermionic emission of carriers across the metal-semiconductor interface. The treatment includes the effect of image force lowering both the thermionic emission and electron tunneling processes. This analysis allowed us to separate and identify the thermionic emission a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…As we showed in our previous works [18,19], the barrier height depends strongly on reverse bias voltage, especially for low reverse bias at low temperatures. In order to obtain the best results, we will omit to use the data that exhibit the reverse bias dependence of barrier height.…”
Section: Resultssupporting
confidence: 63%
“…As we showed in our previous works [18,19], the barrier height depends strongly on reverse bias voltage, especially for low reverse bias at low temperatures. In order to obtain the best results, we will omit to use the data that exhibit the reverse bias dependence of barrier height.…”
Section: Resultssupporting
confidence: 63%
“…This type of contact can be found in SiC and GaN devices. Depending on the barrier height and the thickness, the linear IV characteristic can be achieved due to the thermionic and/or the tunneling transport through the barrier [18]. Irrespective of the band diagram details at the MS interface, the carrier transport through the contact also leads to absorption or release of the heat, since the carriers' thermal equilibrium energy is different on each side of the contact (Figure 3).…”
Section: Metal-semiconductor Interface Basicsmentioning
confidence: 99%
“…They concluded that the thermionic emission (TE) process dominates the current flow under both forward and reverse bias conditions. In our more recent theoretical and experimental works [26,27], we investigated the conduction mechanisms of the leakage current for 4H-SiC SBDs and found that the reverse transition voltage versus temperature plot was strongly dependent on several parameters, namely: doping concentration, barrier height and effective mass. Since the electron effective mass in β-Ga 2 O 3 material is different from that of 4H-SiC material, so, one can expect a significant change in the reverse transition voltage for β-Ga 2 O 3 SBDs.…”
Section: Introductionmentioning
confidence: 99%